Duties and Functions of Police Officers to Overcoming Narcotics Abuse (Al-Ishlah: Jurnal Ilmiah Hukum, 2022)
This study aims to to determine the duties and functions of the Bone Resort Police Officers and the obstacles to overcoming narcotics abuse in Bone Regency. This type of research is empirical legal research. The interview method was used to obtain research data. The data obtained in this study were then analyzed qualitatively. The results show that Police Officers for overcame narcotics abuse in Bone Regency have carried out their duties and functions as regulated in Law No. 2 of 2002 and Law No. 35 of 2009. In addition, efforts to overcome narcotics abuse are more precisely started from pre-emptive (education) and preventive (prevention) efforts before making repressive (eradication) and curative (healing) efforts. However, overcoming narcotics has not been able to maximize as expected by all levels of society. Several factors become obstacles for Bone Resort Police to overcome narcotics abuse, including human resources, budget, and facilities. Therefore, it is recommended for all levels of society, the Bone Regency Government, the Bone Regency Judiciary, and the Bone Regency BNN also take essential duties in overcoming narcotics abuse. Furthermore, it is necessary to increase the budget allocation for Police Officers to maximize the efforts to overcome narcotics abuse in Bone Regency.